9-3x-1=6x+10

Simple and best practice solution for 9-3x-1=6x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3x-1=6x+10 equation:


Simplifying
9 + -3x + -1 = 6x + 10

Reorder the terms:
9 + -1 + -3x = 6x + 10

Combine like terms: 9 + -1 = 8
8 + -3x = 6x + 10

Reorder the terms:
8 + -3x = 10 + 6x

Solving
8 + -3x = 10 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8 + -3x + -6x = 10 + 6x + -6x

Combine like terms: -3x + -6x = -9x
8 + -9x = 10 + 6x + -6x

Combine like terms: 6x + -6x = 0
8 + -9x = 10 + 0
8 + -9x = 10

Add '-8' to each side of the equation.
8 + -8 + -9x = 10 + -8

Combine like terms: 8 + -8 = 0
0 + -9x = 10 + -8
-9x = 10 + -8

Combine like terms: 10 + -8 = 2
-9x = 2

Divide each side by '-9'.
x = -0.2222222222

Simplifying
x = -0.2222222222

See similar equations:

| x/(x+3)=(x-4)/3 | | x^3/15 | | 8+(11/p)=10/p^2 | | 3y-y=-16 | | 4-4(1-4x)=32 | | 2x+2=314 | | 1-2n=n-14 | | 8+11/p=10/p^2 | | -4(-2)+3(4+2(-4))= | | 5t-3=33-t | | -4(t+2)=4 | | 50k+180=40k+120 | | x+34+x+47=69 | | -3(x+4)-6(x-4)=12 | | 24-12x=20 | | 34.95+4x=200 | | 2n^2(5n+3)= | | bw+y=2y | | 5.8(1-6.8p)=246.384 | | (6x^2y^-1/8x^-3y)^2 | | -4(-2)+3(4+2v)= | | -4x+12=-4x+4 | | 4sin^2(x)=1 | | 3X+4X+8X+6X+5X=360 | | (4x-1)+(2x-1)=2x | | -5+6r=4r+1r | | 2/2y=2/2(y-2) | | 8x+9+6x-3=34 | | 5x+6=(4x+7) | | 5p-4p^2=0 | | -6(k+7)=-90 | | x+6=(3-x) |

Equations solver categories